Ca2+ entry via alpha(1G) and TRPV4 channels differentially regulates surface expression of P-selectin and barrier integrity in pulmonary capillary endothelium - Wu, Songwei; Jian, Ming-Yuan; Xu, Yan-Chun; Zhou, Chun; Al-Mehdi, Abu-Bakr; Liedtke, Wolfgang; Shin, Hee-Sup; Townsley, Mary I. (AMER PHYSIOLOGICAL SOC, 2009)
Wu S, Jian MY, Xu YC, Zhou C, Al-Mehdi AB, Liedtke W, Shin HS, Townsley MI. Ca2+ entry via alpha(1G) and TRPV4 channels differentially regulates surface expression of P-selectin and barrier integrity in pulmonary capillary endothelium. Am J Physiol Lung Cell Mol Physiol 297: L650-L657, 2009. First published July 17, 2009; doi:10.1152/ajplung.00015.2009.-Pulmonary vascular endothelial cells express a variety of ion channels that mediate Ca2+ influx in response to diverse environmental stimuli. However, it is not clear whether Ca2+ influx from discrete ion channels is functionally coupled to specific outcomes. Thus we conducted a systematic study in mouse lung to address whether the alpha(1G) T-type Ca2+ channel and the transient receptor potential channel TRPV4 have discrete functional roles in pulmonary capillary endothelium. We used real-time fluorescence imaging for endothelial cytosolic Ca2+, immunohistochemistry to probe for surface expression of P-selectin, and the filtration coefficient to specifically measure lung endothelial permeability. We demonstrate that membrane depolarization via exposure of pulmonary vascular endothelium to a high-K+ perfusate induces Ca2+ entry into alveolar septal endothelial cells and exclusively leads to the surface expression of P-selectin. In contrast, Ca2+ entry in septal endothelium evoked by the selective TRPV4 activator 4 alpha-phorbol-12,13-didecanoate (4 alpha-PDD) specifically increases lung endothelial permeability without effect on P-selectin expression. Pharmacological blockade or knockout of alpha(1G) abolishes depolarization-induced Ca2+ entry and surface expression of P-selectin but does not prevent 4 alpha-PDD-activated Ca2+ entry and the resultant increase in permeability. Conversely, blockade or knockout of TRPV4 specifically abolishes 4 alpha-PDD-activated Ca2+ entry and the increase in permeability, while not impacting depolarization-induced Ca2+ entry and surface expression of P-selectin. We conclude that in alveolar septal capillaries Ca2+ entry through alpha(1G) and TRPV4 channels differentially and specifically regulates the transition of endothelial procoagulant phenotype and barrier integrity, respectively.
Keywords: INDUCED LUNG INJURY; PHENOTYPIC HETEROGENEITY; ION CHANNELS; VASCULAR ENDOTHELIUM; RAT LUNG; PERMEABILITY; CELL; ISCHEMIA; MICE; RESISTANCE